MK Land Sdn Bhd - Saujana Triangle Sdn Bhd / Nur Yasmin Ahmad Yunus - Ahmad Yunus, Nur Yasmin (Faculty of Business and Management, 2023)
Industrial training is work experience required for professional development in advance of graduation. All UiTM students must complete 24 weeks of Industrial Training as part of their academic obligations. During their final semester, students will frequently participate in Industrial Training and will be placed in internship position in any acceptable company of their choice. The training was held at MK Land Sdn Bhd under Saujana Triangle Holding Berhad, and the internship was set to last 24 weeks (6 months), beginning from 1st March and ended on 15 August 2023. The trainee was assigned as a practical trainee during the specified period of time and was obligated to follow the company's rules and regulations. The trainee was mentioned throughout the internship by her designed supervisor, Mrs. Jayanthi, Head of Sales, who was in charge of supervising the trainee. The trainee must maintain good discipline and interpersonal relationships not only with the supervisor, but also with the other employees as well as their supplier. Throughout the six months of my internship, I gained a variety of knowledge and experience such as how to dealing with event organizer, responsible to in-charge an event, how to design and editing and how to manage my time properly. I am going to relate my experience with course that I have taken at university. In additional, I have to complete all the task accordingly and do planning for the next task I assigned to.